Menggali Potensi Ekonomi Kreatif sebagai Sarana Pendukung Desa Wisata - Diyah Sukanti Cahyaningsih; Tonny Suhartono; Sri Widayati (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
Creative economy development in tourist villages is very important. In supporting the existence of a tourist village, homestays and special food souvenirs are the carrying capacity. Study of economic benefits is needed to strengthen the motivation of citizens in developing this creative economy. This Homestay service aims to provide a new source of income for the family. The Community Service Team organizes activities in several stages by prioritizing citizen participation. The service method used is the Community Based Development or Participatory Approach. This method is used to ensure the commitment of citizens to this economic empowerment program. With the participation of residents who are the basis of this program, it is believed that the program will continue after the mentoring period ends. The result of this dedication is the first, the arrangement of the house into a homestay with the category of "in-house". The housing facilities were tidied up and equipped for the benefit of tourists, but did not leave the typical life of the residents as the main attraction. Second, management of typical food packages and chips souvenirs. Residents are given a discourse to make culinary packages that are marketed online to be ordered by prospective tourists who will visit. Taro chips, which are one of the household activities that have been managed in a simple manner, are directed towards better and more attractive management and packaging. In the final stage, an economic study of the homestay and taro chips business is given to calculate the future development of this business.DOI: https://doi.org/10.26905/abdimas.v6i2.5078